Pengembangan Penyapu Magnet Otomatis Menggunakan Sistem IoT - Iwan Susanto; Chi-Yu Tsai; Nurzal Nurzal; M Zalu Purnomo; Ing-Song Yu (Recent in Engineering Science and Technology, 2024)
This study presents a comprehensive analysis of the epitaxial growth and surface characteristics of GaN films on 2D MoS2/c-sapphire substrates. Reflection High Energy Electron Diffraction (RHEED) patterns demonstrate the evolution of the substrate and GaN film surfaces during growth. The subsequent growth of GaN films results in the emergence of hexagonal spots, indicative of a single crystal structure. The brightness intensifies with longer growth times, confirming the improvement in GaN crystalline quality. Atomic Force Microscopy (AFM) images provide further insights into the surface texture. The 2D MoS2/c-sapphire substrate exhibits a textured surface, while GaN films display similar features with bright colors corresponding to GaN clusters. The Root Mean Square (RMS) surface roughness values of GaN films have a higher roughness compared to the substrate. Scanning Electron Microscopy (SEM) confirms the uniform coverage of GaN films, revealing smooth growth and organized hexagonal structures. These findings collectively demonstrate the successful epitaxial growth of GaN films on 2D MoS2/c-sapphire substrates, providing valuable insights into their surface morphology and crystalline structure.